A Case of Cachexia Secondary to Obsessive-Compulsive Disorder. (27th May 2020) - Gosnell, Hailey L.; Kablinger, Anita S.
Abstract : Obsessive-compulsive disorder (OCD), a relatively common psychiatric illness, is diagnosed using DSM-V criteria. Its severity is assessed using the Yale-Brown Obsessive Compulsive Scale (Y-BOCS). Symptoms are broken down into five categories of obsessive-compulsive (O-C) manifestations: contamination/cleaning, symmetry/ordering, taboo thoughts, doubt about harm/checking, and worry about throwing away items that could prove useful or valuable/hoarding. CBT in the form of exposure response therapy (ERP) and/or SSRI/clomipramine administration is the mainstay of treatment. We present a unique OCD case in the nature of obsessions and compulsions, cachexia presentation without anorexia, and history of multiple inpatient psychiatric admissions. Our patient's obsessions focus on eating at specific times, prompting compulsive eating patterns that often result in starvation due to missing timeframes that the patient deems acceptable for eating. His resulting cachexia and eventual worsening of depression to the point of suicidality necessitated multiple inpatient stays and placement at a long-term mental health care facility.